Millennium development goals : advances in environmentally sustainable development in Latin America and the Caribbean - Schaper, Marianne (UN New YorkUS, 2010)
Presents a review of the official indicators of the 7th MDG for LAC since 1990. Summarises the situation in the region for each indicator. Analyses the indicators in depth within the socio-economic and institutional context and against the backdrop of climate change. Sets out some guidelines for progressing towards the achievement of the targets corresponding to the 7th goal.